A magnetic nanoparticle-labeled immunoassay with europium and samarium for simultaneous quantification of serum pepsinogen I and II. Issue 3 (3rd July 2017) - Fan, J.; Xiao, H.; Zhang, J.; Zhou, B.; Deng, L.; Zhang, Y.; Huang, B.
Abstract: Objective: To develop a novel immunoassay for the simultaneous determination of serum pepsinogen I (PG I) and pepsinogen II (PG II) by combining established methods of time-resolved fluoroimmunoassay (TRFIA) and magnetic nanoparticles separation. Materials and methods: This new immunoassay method was characterised by immobilising primary antibodies on the surface of magnetic particles and labelled with stable fluorescent chelates of europium and samarium. Results: Using magnetic nanoparticles, the TRFIA immunoassay exhibited broad dynamic assay ranges for PG I with detection limit of 0.33 ng/mL, while for PG II with detection limit of 0.38 ng/mL. Cross-reactivity between PGs I and II were <15. The intra- and inter-assay coefficient variations of the method were <3%, and the recoveries were in the range of 97–103% for serum samples. Bland–Altman analysis of 124 serum samples showed good consistency with a commercial TRFIA kit. For PG I, the mean (95% confidence interval) difference was 0.97 (–14.3–12.3) ng/mL, whilst for PG II the difference was 0.6 (–4.4–3.2) ng/mL. Conclusions: Our data suggest that the method is feasible and could be developed into a platform for the routine clinical determination of PG I and PG II levels in human serum.